A randomized comparative study of efficacy of microneedling with 5% 5-FU and microneedling with 0.1% tacrolimus in treatment of vitiligo - Shanta Passi; Snehlata Punia; Garima Vinayak (Wolters Kluwer Medknow Publications, 2023)
Background: Vitiligo is an amelanotic disorder affecting 0.5% to 2% of the world's population. Several treatment modalities have been tried and it has been reported that combination therapies augment the repigmentation in vitiligo. Objective: To compare the efficacy of microneedling with 5% 5-FU and microneedling with 0.1% tacrolimus in treatment of vitiligo. Methods: Twenty-five patients with localized stable vitiligo were subjected to microneedling of two patches with dermaroller of size 2 mm, then application of 5-fluorouracil to one patch and tacrolimus on the other patch. This procedure was repeated every month for maximum 6 months (six sessions). The patients were followed up for 3 to 4 months after the last session. Results: The overall repigmentation was slightly higher in 5-FU treated patches than tacrolimus treated patches. Very much improved to much improvement in VASI score was seen in 14 patches (64%) in 5% 5FU treated patches and 11 patches (44%) in 0.1% tacrolimus treated patches. Improved and minimally improved lesions, that is, eight patches (32%) and 11 patches (44%) respectively treated with 5% 5FU and 0.1% tacrolimus. Three patients (12%) showed no improvement. However, there was significant difference between the two drugs, regarding inflammation, ulceration, and hyperpigmentation which occurred with 5-FU. Conclusion: Microneedling combined with 5% 5-fluorouracil or tacrolimus is effective though 5-FU achieved better repigmentation.